STATE REGULATION OF WATER COMPLEX DEVELOPMENT BY IMPLEMENTING AN INTEGRATED APPROACH TO WATER RESOURCE MANAGEMENT ACCORDING TO BASIN PRINCIPLE - Ievdokymov V.O.; Zhuk V.M. (Pressing Problems of Public Administration, 2015)
The problem of water complex Ukraine on the state level analyzed ways of implementing anintegrated approach for water management basin principle.